2003
DOI: 10.1038/sj.onc.1206884
|View full text |Cite
|
Sign up to set email alerts
|

The p53 tumor suppressor gene is regulated in vivo by nuclear factor 1-C2 in the mouse mammary gland during pregnancy

Abstract: The p53 tumor suppressor protein plays an important role in preventing cancer development by arresting or killing potential tumor cells. Downregulated p53 levels, or mutations within the p53 gene, leading to the loss of p53 activity, are found in many breast carcinomas. Here we demonstrate that the p53 gene is transcriptionally upregulated in the normal mouse mammary gland at midpregnancy. We show that the specific isoform nuclear factor 1-C2 (NF1-C2) plays an important role in this activation. Functional muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…p53 is a central component in the protection of the mammary epithelium against tumor progression, and transcriptional control of p53 expression participates in the generation of appropriate levels of active p53 in response to mitogenic stimulation. We have previously provided data showing that NF1-C2 is one of the factors responsible for stimulating p53 gene expression in the mouse mammary gland (14). In the present paper, we extend this information by showing that nuclear Jak2 is important for the expression of p53.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…p53 is a central component in the protection of the mammary epithelium against tumor progression, and transcriptional control of p53 expression participates in the generation of appropriate levels of active p53 in response to mitogenic stimulation. We have previously provided data showing that NF1-C2 is one of the factors responsible for stimulating p53 gene expression in the mouse mammary gland (14). In the present paper, we extend this information by showing that nuclear Jak2 is important for the expression of p53.…”
Section: Discussionsupporting
confidence: 69%
“…We showed by using promoter studies and the in vivo methods chromatin immunoprecipitation and oligonucleotide decoy that binding of NF-C2 to the mouse p53 promoter is important for the expression of p53 at midpregnancy. Furthermore, we have shown that during the development of the mouse mammary epithelial cells, NF1-C2 activates the CEL and whey acidic protein gene promoters (14,16). Since we had shown by siRNA experiments and several other methods that there is a correlation between nuclear Jak2 and the level of NF1-C2, we wanted to investigate if the decrease of Jak2/NF1-C2 had any effect on the expression of the p53 gene and the CEL gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism by which Jak2 increases the amount of active NF1-C2 is independent of the signal transducers and activators of transcription (Stat) pathway, relies on direct interaction between Jak2 and NF1-C2, and involves tyrosine phosphorylation of NF1-C2 and protection against proteasomal degradation (14). The known function for NF1-C2 is to activate p53 and participate in the establishment of expression of milk protein genes during pregnancy (15,16).…”
Section: Introductionmentioning
confidence: 99%